Analisis Karakteristik Pola Sedimentasi dan Perubahan Morfologi Muara Sungai Serayu - Novi Andhi Setyo Purwono; Atiyah Barkah; Didit Triyanto; Prengki Handino (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
Muara Sungai Serayu is located in the Cilacap district, precisely in the Adipala and Kesugihan districts. When the flow of water enters the estuary there will be a change or transition in the speed of the water flow. Slowing water flow causes sedimentation in the river mouth so that sedimentation occurs at the mouth of the river mouth. The mouth of the Serayu river estuary has undergone a morphological change due to the presence of a sand spit that covers the mouth of the river estuary so that it experiences a diversion to the area. From the results of the SED2D modeling there was a change in the base elevation in the mouth of the river mouth with the existing conditions of 11.79% - 30.20%. In the groundsill planning conditions an increase of 0.35%, resulting in a decrease in elevation of 11.56% - 30.55%. Changes in the base elevation in the jetty planning conditions decreased by 0.47% from the existing conditions, so there was a change in evelation for 1 year amounting to 0.06% - 29.73%. Based on the sedimentation pattern that has been modeled on the groundsill planning conditions and jetty planning conditions by considering changes in the base elevation, then what is used as an estuary safety building is a long type jetty. Before planning the jetty, dredging is needed around the mouth of the Serayu River estuary to a depth of -3.00 m. Keywords—Groundsill, jetty, river estuary mouth Serayu, sediment